A New User Dependent Iris Recognition System Based on an Area Preserving Pointwise Level Set Segmentation Approach. (26th April 2009) - Barzegar, Nakissa; Moin, M. Shahram
Abstract : This paper presents a new user dependent approach in iris recognition systems. In the proposed method, consistent bits of iris code are calculated, based on the user specifications, using the user's mask. Another contribution of our work is in the iris segmentation phase, where a new pointwise level set approach with area preserving has been used for determining inner and outer iris boundaries, both exclusively performed in one step. Thanks to the special properties of this segmentation technique, there is no constraint about angles of head tilt. Furthermore, we showed that this algorithm is robust in noisy situations and can locate irises which are partly occluded by eyelid and eyelashes. Experimental results, on three renowned iris databases (CASIAIrisV3, Bath, and Ubiris), show that our method outperforms some of the existing methods, both in terms of accuracy and response time.